If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + -3(x + -5) = 3(x + 1) Reorder the terms: 2 + -3(-5 + x) = 3(x + 1) 2 + (-5 * -3 + x * -3) = 3(x + 1) 2 + (15 + -3x) = 3(x + 1) Combine like terms: 2 + 15 = 17 17 + -3x = 3(x + 1) Reorder the terms: 17 + -3x = 3(1 + x) 17 + -3x = (1 * 3 + x * 3) 17 + -3x = (3 + 3x) Solving 17 + -3x = 3 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 17 + -3x + -3x = 3 + 3x + -3x Combine like terms: -3x + -3x = -6x 17 + -6x = 3 + 3x + -3x Combine like terms: 3x + -3x = 0 17 + -6x = 3 + 0 17 + -6x = 3 Add '-17' to each side of the equation. 17 + -17 + -6x = 3 + -17 Combine like terms: 17 + -17 = 0 0 + -6x = 3 + -17 -6x = 3 + -17 Combine like terms: 3 + -17 = -14 -6x = -14 Divide each side by '-6'. x = 2.333333333 Simplifying x = 2.333333333
| -3x+8x+3+6= | | 1/2(a+8)=6 | | 5x+15=8x+2-8 | | x+5(x)+35+x=385 | | c=38.02+0.25 | | 78=18-5y | | 3n-2=14+2b | | 8v-4=-12+7v | | 0.32x+0.23=0.40x+6 | | -6r=-18 | | Ax+5y=20 | | 3x=1y+2 | | -9+2.5y-0.7+1+6.4y= | | 4(p+7)=36+5p | | 7z+8=6z | | (2-7x)=(2x+1) | | 4(x+7)=36+5p | | 18-12x=-22-7x | | 3p(r+1)=7r-8t | | 7p-3=34 | | 12-36x-6x-24=-12 | | 5(9x-5)+12x= | | g(2)=7x-4 | | 2x+3y=4z-3xy | | 5a+35-12a-3=12-12a | | 2+3(-8n+6)=116 | | 125+15m=800 | | 10x+90=8x | | 3+(6x+4)=9 | | 2x+x-250=2858 | | 3(3Y-5)Y=-15 | | 8y-5x=27 |